Southey’s “German Sublimity” and Coleridge’s “Dutch Attempt” - Chandler, David (Romanticism on the Net)

(untitled) (Université de Montréal, 2003)
AbstractSouthey’s public criticism of “The Ancient Mariner” as “a Dutch attempt at German sublimity” is conventionally and all too easily dismissed as a demonstration of his limitations, both as a man and as a poet. Given Southey’s allegiance to the tradition of “German sublimity,” which he felt was epitomized in Bürger’s ballads, and which he found championed by his literary friends in Norwich, he had good grounds for concern at Coleridge’s redevelopment of the modern ballad, however. Southey’s own ballad, “The Old Woman of Berkeley,” is read here as a deliberate “answer” to the problems he found in “The Ancient Mariner,” and an attempt to reinforce the “sublime” Bürger tradition. The most important difference concerns the poets’ attitudes to the past, which to Southey is essentially dead, and in need of the poet’s “organicizing” voice (Geoffrey Hartman’s term), while to Coleridge its imaginative energy survives, and can be mediated by the poet. This difference puts Southey closer to the German brand of “Romanticism.” The issues between Southey and Coleridge here are relevant to the problems we face today as scholars approaching, sorting, and evaluating the narratives of the past.